2014
DOI: 10.1007/s10753-014-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Potential Regulatory Role of IL-17F in Pathogenesis of Chronic Periodontitis

Abstract: The objective of this study was to investigate the expression level, clinical significance, and possible regulating role of IL-17F in patients of chronic periodontitis. Periodontal local tissues were obtained from chronic periodontitis (CP) and healthy controls (HC) for real-time PCR (RT-PCR) detection with IL-17F and IL-17A messenger RNA (mRNA). Primary human gingival fibroblasts (HGF) were derived from patients receiving crown-lengthening procedures. Efficiency of small interfering RNA (siRNA) of IL-17R to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Thus, we propose that miR‐144‐5p might regulate the chronic periodontal inflammation progression via COX2 , IL17F or other autophagy‐related genes in the autophagy process. However, both COX2 and IL17F showed downregulated expression at the mRNA level in the chronic periodontitis group, which contradicted to previous results . The reason for different results in this study might be that, in our study, gingival tissues were collected after initial periodontal treatment and this could have an effect on the inflammation condition of the periodontium.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Thus, we propose that miR‐144‐5p might regulate the chronic periodontal inflammation progression via COX2 , IL17F or other autophagy‐related genes in the autophagy process. However, both COX2 and IL17F showed downregulated expression at the mRNA level in the chronic periodontitis group, which contradicted to previous results . The reason for different results in this study might be that, in our study, gingival tissues were collected after initial periodontal treatment and this could have an effect on the inflammation condition of the periodontium.…”
Section: Discussioncontrasting
confidence: 94%
“…The genes encoding important molecules involved in periodontal inflammation identified in previously published articles include matrix metallopeptidases including MMP1 , MMP2 , MMP3 , MMP8 , MMP9 and MMP13 and tissue inhibitors of metalloproteinases including TIMP1 , TIMP3 and TIMP4 ; various interleukin (IL) families including IL1 β, IL2 , IL4 , IL6 , IL8 , IL10 , IL11 , IL 12 , IL17A , IL17F , IL18 , IL21 , IL23 and IL35 ; the pentraxin family including C‐reactive protein/pentraxin 1 ( CRP / PTX1 ) and pentraxin 3 ( PTX3 ); the TNF superfamily TNF‐ α and the receptor activator of the NFκB ligand/TNF superfamily member 11 ( RANKL / TNFSF11 ); the TNF receptor superfamily osteoprotegerin/TNF receptor superfamily member 11b ( OPG / TNFRSF11B ); the transforming growth factor (TGF) superfamily TGF β 1 ; the TLR family including TLR2 and TLR4 ; chemokines including C‐C motif chemokine ligands ( CCL2 , CCL3 , CCL5 , CCL19 , CCL20 ), C‐C motif chemokine receptor 4 ( CCR4 ) and C‐X‐C motif chemokine ligands ( CXCL6 , CXCL8 / IL8 ); suppressors of cytokine signalling including SOCS1 and SOCS3 ; interferon IFN‐ γ; transcription regulator T‐box 21 ( TBX21 ); NF κ B / NFKB1 ; TNF‐α‐induced protein 3 ( TNFAIP3 ); peptidylprolyl isomerase A/cyclophilin A ( PPIA / CypA ); and cyclooxygenase 2/prostaglandin‐endoperoxide synthase 2 ( COX2/PTGS2 ) . By combining the retrieval and computer algorithm prediction results, potential target genes related to periodontal inflammation were determined.…”
Section: Methodsmentioning
confidence: 99%
“…The IL-6 expression was found in serum and saliva of OLP patients (51) and was considered indicative of a Th2 cellular involvement in OLP (22,42), which was involved in the initial reaction of OLP pathogenesis (1). Similarly, as an important NF-kappaB cytokine, IL-6 has been regarded as a bridge in linking inflammatory disease to cancer (52), which can be greatly induced by IL-17 family cytokines like IL-17A or IL-17F (53). Furthermore, we tested the NF-kappaB-associated pro-inflammatory cytokines in OLP patients and found IL-6, IL-8, and TNF-a all significantly increased in OLP salivary and serum (25,54).…”
Section: Th1/th2 Imbalance In Olp Pathogenesismentioning
confidence: 99%
“…Previous studies have shown increased CCL20 expression by epithelial cells stimulated with P. intermedia , by P. gingivalis and F. nucleatum . This chemokine has also been documented in periodontitis tissues, with elevated levels linked to increased numbers of dendritic cells in diseased sites and elevations in expression of IL‐17‐related chemokines including CCL20 . IL‐23 activates STAT4 within the JAK‐STAT signaling cascade inducing interferon‐γ, preferentially targeting memory CD4 + T cells and promoting the production of various proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 88%
“…76 This chemokine has also been documented in periodontitis tissues, with elevated levels linked to increased numbers of dendritic cells in diseased sites 77 and elevations in expression of IL-17-related chemokines including CCL20. 78 IL-23 activates STAT4 within the JAK-STAT signaling cascade 79 inducing interferonγ, preferentially targeting memory CD4 + T cells and promoting the production of various proinflammatory cytokines. Information on this cytokine in periodontitis is rather limited, but may have a role in the cytokine cascade of granuloma tissues 80 and in responses of periodontal ligament cells to LPS.…”
Section: Effects Of Environmental Lead On Epithelial Responses To Amentioning
confidence: 99%